Analysis of Consumer Behavior Towards the Use of Single-Use Plastics in Tourist Areas on the Island of Bali - Zahra Jannatul Firdausi; Abdur Rohman (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
This study aims to analyze consumer behavior towards the use of single-use plastics in tourist areas in Bali. Plastic waste has become a serious problem, especially in beach tourism areas where cleanliness and comfort are important aspects. This study identifies the factors that influence tourists' decisions in purchasing plastic-packaged products in beach tourism areas. Tourism involves the temporary relocation of individuals to locations outside their place of residence, and plastic waste in beach tourism areas is a significant concern. This research focuses on tourist behavior related to the purchase of plastic-packaged products in beach tourism areas.